City minimum wages and spatial equilibrium effects - Jorge Pérez Pérez (Banco de México, 2022)
This paper studies the effect of minimum wage changes on spatial equilibriums in local labor markets. Using data for the U.S. and minimum wage variation across state borders, I analyze how commuting, residence, and employment locations change in response to local minimum wage changes. I find that areas where the minimum wage increases receive fewer low-wage commuters. I formulate a spatial equilibrium model and calculate counterfactuals with a higher minimum wage for U.S. cities considering an increase. For small minimum wage increases, most counties would receive higher lowwage commuting and have fewer low-wage residents. As minimum wage increases are larger, there are higher low-wage commuting reductions driven by employment relocation.
Keywords: J31; J38; R23; 330; Minimum wage; spatial equilibrium; local labor markets